Dimension of Human Rights Protection Against Corporate Crimes - K. Kristian (Sociological Jurisprudence Journal, 2022)
The wave of influence of Neoliberalism and globalization with its system of economic capitalism has begun to change the economic ideology by ignoring sound principles in business dealings (there is even a tendency to put forward the â€œanomie of successâ€ principle), a considerable number of corporations have committed acts in violation to human rights. This paper is going to examine the implementation of human rights-based protection and law enforcement. It has now become significant considering how critical thinking in solving corporate human rights violation problems is urgently needed. The type of approach used by the writer in this research is the Normative Law Research Method. The methods applied will consist of statute approach, case approach and conceptual approach. Research shows that Indonesia is a country of law. By this concept, principles contained in that country must be applied, one of them being the presence of the acknowledgement and protection of basic human rights. In the context of a country with Pancasila as its main law, the effectual supremacy of law in Indonesia must continually be done within a framework which focuses in creating public welfare and social justice for all Indonesian people. In this context, the human potential and dignity have a high and noble position. Regulation governing the protection of human rights may be found in the Universal Declaration of Human Rights, the 1945 Constitution of the Republic of Indonesia and the 1999 Act of the Republic of Indonesia No. 39 concerning Human Rights. These human rights have frequently been violated by corporations while conducting their business activities. In international legal instruments, The United Nations Global Compact (UNGC) exists as an initiative to strategic policies for corporations to make a commitment which will align their policies and strategic operations with the ten universal principles of human rights, labor, environment and anti-corruption, in order to allow sustainable business practices. Within the sphere of human rights, the UNGC states that â€œbusiness should support and respect the protection of internationally proclaimed human rightsâ€ and â€œmake sure that they are not complicit in human right abusesâ€, along with other alternatives that may be conducted by the corporations. For that, the country has a responsibility to provide devices by utilizing all its resources to create equality, non-discrimination and human rights protection for every citizen. The country has to do its part to calculate every possible way to allow for human rights protection and to facilitate the recovery over losses that may arise from the violation of human rights, especially those done by corporations.